Disciplining India: paternalism, neo-liberalism and Hindutva civilizationalism. (6th March 2023) - Chacko, Priya
Abstract : Policy hybrids combining neo-liberal and national-developmentalist goals are rising. Examining India's policy hybrids, this article argues that a 'paternalist political rationality' driven by neo-liberalism and Hindutva civilizationalism underpins India's flagship economic policies and may ultimately undermine its global ambitions. Abstract: Policy hybrids, which combine marketizing and liberalizing reforms with social welfare programmes and state support to boost domestic production, are fast becoming the norm globally. How are neo-liberal and national-developmentalist agendas reconciled as governing practices, and what are their national and international outcomes and implications? This article focuses on the understudied case of India, arguing that a paternalist political rationality, which melds paternalist logics in neo-liberalism and the government's Hindutva civilizationalist politics, underpins its flagship economic policy, the Atmanirbhar Bharat Abhiyan (Self-reliant India Mission). This policy, through production-linked incentives, aims to boost Indian manufacturing. India has benefited from a global push to diversify supply chains and forge new geopolitical partnerships, such as the Quad, to undermine China's manufacturing dominance and geopolitical assertiveness. Yet, its current approach consolidates the dominance of large firms, producing an elitist political economy, and does not address structural weaknesses through public investment in areas like research and education. This has implications for India's development, global trade and geopolitics. These arguments are made by identifying the paternalist logics in the theories and practices of neo-liberalism, and in Hindutva civilizationalist politics; assessing the aims of the Atmanirbhar Bharat Abhiyan as elaborated by government officials; and evaluating the early outcomes of production-linked incentive schemes.